Effective Management of Hyperglycemia Improve the Outcome of Aneurysmal Subarachnoid Hemorrhage - Husnain Hashim (Pakistan Journal of Medical & Health Sciences, 2022)
Aneurysmal subarachnoid hemorrhage is one of the most commonly known life-threating disease. Many neurological outcomes are associated with SAH. The poor outcomes are associated with the hyperglycemia in the aneurysmal subarachnoid hemorrhage patients. The major risk factor associated with the aneurysmal subarachnoid hemorrhage is hyperglycemia. Objective: The purpose of this research work was to get in-depth understanding of the effect of glycemic control on changes in the outcomes associated aneurysmal subarachnoid hemorrhage. Study design: It is a prospective study with the statistical approach, conducted at Department of Neurology, Fauji Foundation Hospital, Rawalpindi. Methods: The 365 patients visited the neurology department of our institute were included in the study. The duration of this study was March 2020 March 2022. The 56 ± 14 years was the mean age of the patients included in this study. The 106 (29%) out of 365 were male candidates. The half of the patients were treated with the aggressive hyperglycemic management AHM protocol, while other half were treated with the standard glycemic management SGM protocols. The patients was labelled with good glycemic outcome if the mean glucose burden is less than 1.1, and labelled as poor outcome if mean glucose burden is greater than 1.1. The outcomes of the AHM and SGM group were compared. Different logistic regression models were used to quantify the poor outcome effects. Results: The result depicted that the patients treated with the AHM protocols showed lower poor outcomes (28%) as compared to the other treated with SGM. The values remain insignificant after correction of temporal trends. The incidence of the poor outcome can be reduced by the good glycemic control. The clinical vasospasm rates remain same before or after the implementation of AHM controls. Conclusion: The poor outcomes associated with the SAH can be reduced by good glycemic control of the patients. The study depicted the not only the blood glucose level will remain in the range but also better neurological health of the patients’ will be promoted by an effective use of aggressive glucose management on the patients suffering from SAH. Keywords: Aneurysmal subarachnoid hemorrhage, AHM glycemic control, Hyperglycemic outcomes, Vasospasm, logistic regression models.